Stability of hysteretic controlled voltage source converters in a power system - Ghosh, Arindam; Ledwich, G. (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
This paper develops a tool for the stability analysis of hysteretic controlled voltage source converters that are connected to a power system. Each VSC is controlled by a state feedback control input to a hysteretic comparator. A suitable model of the converter is first developed by including the state feedback gains and hysteretic switching controller design. The model is then extended to incorporate parallel operation of two VSCs. To consider autonomous operation, droop controllers are incorporated in the model. A linearized model of the system is developed for eigen analysis. It has been shown that the system response predicted by the developed model matches PSCAD simulation results very closely. Since hysteretic control is widely used for commercial converters, the model developed can be used as an analytical tool.